Internet Marketing On Buying Decisions - Wijayanto, Gatot; Jushermi; Pramadewi, Arwinence; Novandalina, Arini; Rivai, Yutiandry (Journal of Management, 2024)
The purpose of this research was to ascertain the ways in which customer choices to purchase a range of items from Anna Collection on Anna Collection were impacted by online marketing and product quality. The population of this study, which included 138 participants using purposive and non-probability selection, consists of Anna Collection consumers who are residents of the collection. The partial least square is a technique for data analysis in this research, while the survey method is utilized to gather data. The results of research show that internet marketing has a major beneficial influence on purchase choices in addition to the quality of items having a big and positive effect. The study's conclusion is that although purchase choices are more worthwhile, internet marketing is getting more beneficial. Additionally, the quality of the Anna Collection objects improves with the choice to buy them